Agents of Change: An Analysis of Gender Planning for Development in Africa at the Canadian International Development Agency - Acquah, Augusta (Université d'Ottawa / University of Ottawa, 2012)
The thesis examines how the social construction of African women in development discourse transformed from the 1970s to the 2000s, focusing in particular on the Canadian International Development Agency (CIDA). From the 1970s to the 1990s representations of African women were based on women’s economic potential. The mainstreaming of gender in the 1990s resulted in women being represented as agents of change. This approach gave women an opportunity to play roles in decision-making but led to policies that failed to challenge the established institutions. The emphasis on women as agents of change opened doors to some African women but with implications for the women’s movement. Only some middle-class women appear to benefit but their gains have been marginal in comparison to the gender inequalities that persist. The thesis uses secondary sources and interviews with development practitioners in Ottawa to understand the representation of African women as agents of change.
Keywords: Canadian International Development Agency; CIDA; African women; gender and development; gender policy; gender specialists; African women's movement; NGOs; development organizations in Ottawa; women's groups